Response of Okra Plant to Subsurface Drip Irrigation Using Mixed Agricultural Drainage Water - Al-Molhem, Yousef Abdulaziz (2009)
Agriculture in arid areas with its limited water resources will tremendously benefit from drip irrigation. Subsurface drip irrigation system applies water below the soil surface through emitters. It has many advantages over surface drip including better use of low quality drainage water. However there is a need to determine the best irrigation rate and placement of the emitters such that optimal yield can be obtained. A study was carried out to see the response of various moisture regimes supplied through subsurface drip irrigation system using mixed drainage water on the growth and yield of okra Abelmoschus esculentus (Climson Spineless CV). An experiment was conducted during November 2006 to May 2007 inside a greenhouse in the Agriculture Research Station at the University of King Faisal in Al-Hasa, Saudi Arabia. The experiment was laid out following a split plot design. The experiment was divided into two main categories of fresh water and mixed-drainage water. Every category consisted of three water quantities (WQ) viz. V1=100%, V2=75% and V3=50% of the water needs. Every water quantity had three replications R1, R2, and R3. Every replication was divided into five irrigation emitter lateral depths D0 cm, D10 cm, D20 cm, D30 cm, and D40 cm. Statistical analysis was performed for all crop performance parameters. The effect of irrigation emitter lateral depths on okra growth parameters such as plant height, number of leaves per plant, okra moisture, root zone width, root zone depth, okra fruit diameter, and average weight of single okra fruit were analyzed. Results were compared for various irrigation emitter lateral depths (LD) and water quantities (WQ) applied. Irrigation emitter lateral at 10 cm depth was found to be the best to grow okra plant using both fresh and mixed drainage water due to higher concentration of roots even with deficit irrigation supplying only 73% of the required water quantity. Yields were lower with emitters at depths of 30 cm and 40 cm due to lower concentration of roots as the root zone width decreased from the ground to D40 cm. The emitter placement beyond 20 cm depth is not recommended for the okra plants, as the root concentration is less beyond that depth. The average okra plant height with full irrigation using fresh water and emitters at the soil surface was 23 cm; however, it was 31 cm using the mixed water, probably due to some salts present in the mixed drainage water. The study showed that good okra harvest is still possible with mixed drainage water at 4.2 dS/m applied using only about three-quarter of the irrigation water requirement as compared to 2.2 dS/m for fresh water. The possibility of using mixed drainage water under deficit irrigation will increase the water availability for agriculture in arid areas. Consequently, better fresh water conservation is possible. A drip irrigation system design that can be considered as a typical system to grow okra plant in arid areas was developed in this study. The results of the experiment and the crop production models achieved from the statistical analysis provide a good example for growing okra using mixed drainage